The relationship between by stander participation behavior and innovative capability in the Malaysian hotel industry / Nesin Elizabeth Kinat and Noormala Amir Ishak - Kinat, Nesin @ Elizabeth; Amir Ishak, Noormala (Universiti Teknologi MARA, Kedah, 2018)
Innovative capability is one of the requirements for organizations to compete, to survive and to succeed in the global competitive environment. Literature shows that there is no single factor for innovative capability success, but it does recognize that it is possible for every organization to discover where the increased efforts must be focused in order to transform a specific success in a process of continuous innovation and to achieve good results. Therefore, this study proposed the concept of bystander participation behavior on innovative capability in the Malaysian hotel industry. The study is a quantitative method, which tested the relationships between bystander participation behavior and innovative capability. Questionnaires were distributed to more than 500 supervisors from four and five star rated hotels in Malaysia registered in the directory of Malaysian Association of Hotels, of which 208 usable questionnaires were considered valid. Statistical evidence was found that there is a significant relationship between bystander participation behavior and innovative capability.